2017
DOI: 10.1016/j.sjbs.2016.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineered silver nanoparticles using Curvularia pallescens and its fungicidal activity against Cladosporium fulvum

Abstract: Microorganisms based biosynthesis of nanomaterials has triggered significant attention, due to their great potential as vast source of the production of biocompatible nanoparticles (NPs). Such biosynthesized functional nanomaterials can be used for various biomedical applications. The present study investigates the green synthesis of silver nanoparticles (Ag NPs) using the fungus Curvularia pallescens (C. pallescens) which is isolated from cereals. The C. pallescens cell filtrate was used for the reduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 51 publications
1
17
0
1
Order By: Relevance
“…P. radicina was isolated in the root surfaces of soybean [27]. C. pallescens was found on the surfaces of banana fruits [28], in cereals [29], and on the Fig. 4 The causal relationships among DSE species, T. viride, root morphology and plant aboveground morphology based on structural equation model (SEM).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…P. radicina was isolated in the root surfaces of soybean [27]. C. pallescens was found on the surfaces of banana fruits [28], in cereals [29], and on the Fig. 4 The causal relationships among DSE species, T. viride, root morphology and plant aboveground morphology based on structural equation model (SEM).…”
Section: Discussionmentioning
confidence: 99%
“…P. radicina was isolated in the root surfaces of soybean [ 27 ]. C. pallescens was found on the surfaces of banana fruits [ 28 ], in cereals [ 29 ], and on the leaves of Lippia sidoides and Humboldtia brunonis [ 30 , 31 ]. P. herbarum was observed in the roots of salt-stressed soybean plants [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, nanoparticles have achieved remarkable attention as novel antimicrobial products as they possess high surface area-to-volume ratio and unique physical and chemical properties. [7][8][9][10] The different metals including silver, copper, titanium, zinc, and gold are used as antimicrobial materials. Hernándezsierra et al compared the anti-Streptococcus mutans activity of nano scale silver, gold, and zinc oxide and found that silver nanoparticles (AgNPs) worked best.…”
Section: Introductionmentioning
confidence: 99%
“…The successful formation of Ag NPs was verified using various analytical techniques UV–vis, XRD, TEM, and EDS measurements. Myco-synthesis Ag NPs was tested for antifungal effect against eight species of Fusaria causing damping-off of cotton seedlings ( Elgorban et al, 2017 , Yassin et al, 2017a , Yassin et al, 2017b ). The study aimed to eradicate pathogenic plant microorganisms without using synthetic chemical.…”
Section: Introductionmentioning
confidence: 99%